Pengaruh Penerapan Gaya Megajar Latihan Terhadap Peningkatan Kemampuan Gerak Dasar Menendang Bola Dengan Kaki Bagian Dalam Permainan Sepak Bola Pada Peserta Didik SMP Negeri 3 Tenga - Gabriel Andre Igir (STIKES Columbia Asia Medan, 2025)
This study aims to test the effect of applying the teaching style of exercise on the improvement of basic movement skills in kicking the ball with the inside of the foot in soccer games at SMP Negeri 3 Tenga. This research uses an experimental method with a pre-test and post-test randomized control group design. The research sample consists of 20 students, divided into two groups: the experimental group, which receives the treatment using the teaching style of exercise, and the control group, which does not receive the treatment. The results of the study show that the application of the teaching style of exercise has a significant effect on improving the ability to kick the ball with the inside of the foot, with the experimental group showing better improvement compared to the control group. This study concludes that the teaching style of exercise is effective in improving the basic movement skills of kicking the ball in students.